2021
DOI: 10.3390/ijerph18158203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Vaping-Associated Lung Injury Outbreak through Participatory Surveillance and Archival Internet Data

Abstract: The US Centers for Disease Control and Prevention alerted of a suspected outbreak of lung illness associated with using E-cigarette products in September 2019. At the time that the CDC published its alert little was known about the causes of the outbreak or who was at risk for it. Here we provide insights into the outbreak through analysis of passive reporting and participatory surveillance. We collected data about vaping habits and associated adverse reactions from four data sources pertaining to people in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Research showed that 80% of lung injury caused by the consumption of vaping or E-cigarette s is due to the presence of a toxic substance named THC. Almost 58% of lung injury cases are related to the consumption of nicotine and THC, while 13% of cases are reported to have the presence of nicotine only (Hswen and Yom-Tov, 2021). According to reports published by US Food and Drug Administration, E-cigarette s contain vitamin E acetate, which when heated and aerosolized can release a substance named ketene.…”
Section: Possible Reasons and Symptoms Of Vapingmentioning
confidence: 99%
“…Research showed that 80% of lung injury caused by the consumption of vaping or E-cigarette s is due to the presence of a toxic substance named THC. Almost 58% of lung injury cases are related to the consumption of nicotine and THC, while 13% of cases are reported to have the presence of nicotine only (Hswen and Yom-Tov, 2021). According to reports published by US Food and Drug Administration, E-cigarette s contain vitamin E acetate, which when heated and aerosolized can release a substance named ketene.…”
Section: Possible Reasons and Symptoms Of Vapingmentioning
confidence: 99%